Dark Tide: Waterfire Saga #3 - Donnelly, Jennifer (Los Angeles : Disney-Hyperion, 2015)
"Astrid struggles with a shameful secret, Ling discovers courage in a prison camp, and Serafina lines up allies to help fight the final battle for her underwater realm"--
Keywords: Mermaids -- Fiction; Supernatural -- Fiction; Good and evil -- Fiction; JUVENILE FICTION / Social Issues / Adolescence; JUVENILE FICTION / People & Places / General; JUVENILE FICTION / Love & Romance